2016
DOI: 10.4269/ajtmh.15-0574
|View full text |Cite
|
Sign up to set email alerts
|

Local Production of a Liquid Direct Agglutination Test as a Sustainable Measure for Control of Visceral Leishmaniasis in Sudan

Abstract: Abstract. A prerequisite for the control of visceral leishmaniasis (VL) is the accessibility to reference diagnostics. The high price of the freeze-dried direct agglutination test (FD-DAT) and the short shelf-life time of the rK39 strip test (rK39) have limited the application of these tests in Sudan. An original liquid DAT (LQ-DAT) with high reproducibility compared with the FD-DAT and rK39 has been routinely produced in our laboratory since 1999. In this study, a 3.4-year-old batch (of more than 90 test batc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…Our in-house AQ-DAT had a sensitivity (97.3%) comparable to FD-DAT (99.1%) and rK39-ICT (96.5%), taking microscopy as gold standard. This is similar to a study done in Sudan in which AQ-DAT, FD-DAT, and rK39 showed a sensitivity of 99, 95.8, and 79.2%, respectively [14]. Similarly, studies conducted in Brazil and Sudan documented better sensitivity of FD-DAT (98-100%) compared to rK39-ICT (85.7-90%) [20,21].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our in-house AQ-DAT had a sensitivity (97.3%) comparable to FD-DAT (99.1%) and rK39-ICT (96.5%), taking microscopy as gold standard. This is similar to a study done in Sudan in which AQ-DAT, FD-DAT, and rK39 showed a sensitivity of 99, 95.8, and 79.2%, respectively [14]. Similarly, studies conducted in Brazil and Sudan documented better sensitivity of FD-DAT (98-100%) compared to rK39-ICT (85.7-90%) [20,21].…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, another study from the Northeast of Sudan showed, lower sensitivity for FD-DAT (84%) compared with rK39-ICT (93%) [22]. Overall, the observed differences in sensitivity among studies could be due to the strain variation that affects the gene expression level of The specificity of the in-house AQ-DAT, FD-DAT and rK39-ICT were 98.8, 97.5 and 93.2%, respectively, which is in line with findings of the studies done in Sudan which revealed 100, 100 and 97.6%, respectively [14,21]. The AQ and FD-DAT, also showed similar specificity with the findings reported from the United Kingdom, Brazil and Sudan [20,21,23].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Some studies performed DAT using both freeze-dried (FD) and aqueous (AQ) antigen (18,19). No signi cant difference in the sensitivity of the DAT (FD and AQ) was found.…”
Section: Resultsmentioning
confidence: 99%
“…In overall, studies had a wide geographical distribution and were carried out in different countries including Brazil (20)(21)(22), Ethiopia (14,16,23), India (19,(24)(25)(26)(27)(28)(29), Iraq (30), Iran (31-33), Saudi Arabia (15), Sudan (18,(34)(35)(36)(37), Turkey (17) and Venezuela (38).…”
Section: Resultsmentioning
confidence: 99%